IMPORTANCE OF PEDAGOGICAL SOFTWARE IN DEVELOPING THE PROFESSIONAL AND PEDAGOGICAL PREPARATION OF STUDENTS - Shakhlo Mirzayeva Abdurakhmanova (American Journals, 2024)
The article mentions that the era of informatization, which covers all aspects of social life, poses unique problems in the field of education, and the use of open information systems is considered one of the most important tasks of informatization and technologization of modern education, as well as the current Pedagogical software tools have been developed to solve this problem, and it is analyzed that they allow using new approaches in teaching, but they do not always meet modern requirements. At the same time, it is noted that the analysis of pedagogical literature and the study of the experience of various educational institutions show the lack of practice-oriented provision of pedagogical software for educational subjects. This observation indicates the need to develop pedagogical software.
Keywords: Pedagogical programs, electronic textbooks, Internet systems, IT, learner, quality, control.